Implementasi Etika Bisnis Dan Good Corporate Governance Pada Perkebunan Karet PT. Timbang Deli Indonesia - Siti Difyanti (Yayasan Rahmat Islamiyah, 2023)
This study aims to determine how the application of business ethics and good corporate governance of rubber plantations at PT. Timbang Deli Indonesia. The research used is descriptive qualitative research. The data collection method used is the method of observation, interviews and documentation, conducted on the rubber plantation of PT. Timbang Deli Indonesia. With several informants, namely Manager, Office Staff, and several employees. The results of this study indicate that based on interviews by informants that the application of business ethics to employees at the rubber plantation of PT. Timbang Deli Indonesia is very good at carrying out the duties of the company.